Brine sludge waste from a Chlor-alkali industry: characterization and its application for non-structural and structural construction materials - Juliana de Carvalho Izidoro; Denise Alves Fungaro; Luciana Cristina Viviani; Rogério da Costa Silva (Journal of Applied Materials and Technology, 2021)
Brine sludge (BS) is an industrial waste generated in large amounts by the Chlor-alkali industry and, usually disposed into industrial landfills. Because BS contains several chemical compounds, also presents a potential environmental impact. The feasibility of the utilization of brine sludge wastes for the preparation of value-added materials was investigated. The characterization of two brine sludge samples was performed in terms of chemical and physical composition, particle size distribution, X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and thermal analysis (DTA/TG). Elements like Ca, Si, Na, Mg, Al, Cl, and Fe were identified in the samples. The XRD results confirmed the crystalline nature of compounds and indicated that the main compounds in brine sludge samples were calcium carbonate, sodium chloride, magnesium hydroxide, and quartz. FTIR showed the presence of varying functional groups like carbonate, siloxane, and hydroxide. The two brine sludge samples can be considered as a fine powder with the mean diameter (d50) of 4.984 µm and 24.574 µm, for the BS from Santo André and Cubatão, respectively. The results indicated that the brine sludge samples presented favorable characteristics to use limestone ?ller and binder alternative to Portland cement in the nonstructural construction materials. The incorporation of brine sludge in geopolymeric materials is another possible use in sustainable construction material products. The production of value-added products from brine sludge will be an important contribution towards sustainable development adopted by the Chlor-alkali industry.